A comparison of the National Institute for Health and Care Excellence (NICE) and European Association of Urology (EAU) guidelines for the assessment and management of urinary incontinence in women. (March 2018) - Warner, Ross M; Greenwell, Tamsin J
Objective: The objective of this paper is to identify the similarities and key differences between the National Institute for Health and Care Excellence (NICE) and European Association of Urology (EAU) guidelines on the management of urinary incontinence (UI) in women. Methods: We reviewed the most recent iterations of both full guidelines to identify all key recommendations and their associated level/grade of evidence. Guidance on the management of urinary incontinence in men and neuropathic patients was excluded. Results: There is a significant overlap in the recommendations of both guidelines. Key differences include the indications for performing urodynamics, pharmacological agents in stress UI, the dose of botulinum toxin A (200 units by NICE, 100 units by EAU), the hierarchy of surgical options for primary stress UI and the role of the multi-disciplinary team (MDT). Conclusion: This review provides the various stakeholders involved in the management of female UI with a summary of the strength of evidence supporting the recommendations by these two key guidelines. We have provided an evidence-based framework to support clinical experience from which to base management decisions.